High Temperature Conductive Stability of Indium Tin Oxide Films - Li, Haiou; Guo, Lei; Liu, Xingpeng; Sun, Tangyou; Li, Qi; Zhang, Fabi; Xiao, Gongli; Fu, Tao; Chen, Yonghe (Frontiers in Materials, 2020)
Indium tin oxide (ITO) has been studied in applications at normal high temperature below 600 °C, due to excellently electrical characteristics. Attempts to further match the needs of electronics in extremely harsh environments, the changes in the conductive properties of ITO films and its mechanism were investigated at special high-temperature above 1000 °C. ITO films were prepared by pulsed laser deposition (PLA) on lanthanum gallium silicate (LGS) substrates. Furthermore, the as-deposited samples were annealed at different temperature-time treatments, and investigated the effects of annealing on the electrical, structure, surface morphology and chemical properties of ITO films by X-ray diffraction analysis, scanning electron microscopy (SEM), resistance measurement, and X-ray photoelectron spectroscopy (XPS). The experimental results present that the decreased resistance of ITO films was mainly attributed to the increase of the crystalline size and the increased amount of Sn 4+ ions during the heating-up period (0 °C to 1000 °C). Generally, The ITO film showed stable electrical properties when it was heated at the temperature of 1000 °C for at least 2.5hours. The expected ITO films that remain steady above 1000 °C have potential applications as electrodes working in special high-temperature environments.